(untitled) - 1972-; Fanning, Elle; 1998-; 1977-; Ejiofor, Chiwetel; Pfeiffer, Michelle; 1957-; Roenning, Joachim; Woolverton, Linda; 1948-; Jolie, Angelina; 1975-; et al. (Disney, 2020)
Maleficent and Aurora form new alliances and face new adversaries in their struggle to protect the moors and the magical creatures that reside within.
Keywords: Queens; Drama; Good and evil; Drama; Magic; Drama; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Feature films; Fantasy films; Childrens films